Kerajinan Tangan Decoupage dari Bahan Bekas - Ria Novianti; Roza Linda; Nana Rahayu; Ni Putu Nita Wijayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Community Service activities decoupage handicraft training from used materials is carried out on the basis of community conditions, especially women who are members of the Tim Penggerak PKK of Central Tangkerang Village marpoyan Damai District, Pekanbaru is classified as less productive, while they have quite a lot of free time. In addition, in the environment where these mothers live, there is also a lot of household waste such as cans and glass bottles that are thrown away and not used anymore. Community Service activities carried out using demonstration and training methods are an effort by The Community Service Team to be able to empower and improve the knowledge and abilities of PKK members. The use of used goods as a basic material that will be created with decoupage techniques makes the resulting product has good aesthetic value and selling value. The score obtained by participants before the implementation of the study was 51.60%, while after the training was carried out was 98.3% so it can be concluded that the training provided a significant improvement in the ability of participants in making decoupage handicrafts.